TINJAUAN YURIDIS TERHADAP PENGULANGAN TINDAK PIDANA PENCABULAN ANAK - Widia Fransiska (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTWIDIA FRANSISKA 13.11.1001.1011.181 Juridical Review on Repetition of Child Abuse Crime (Case Study of Decision Number: No. 797 / Pid.Sus / 2015 / PN.Samarinda) under the guidance of the Mrs.Kunti Widayati, SH, M.Humas mentor I and The Mr.SyamsulBahri, SH, M.Humas mentor II.This study aimed to determine the inspection process juvenile justice withthe accused who committed the crime of abuse is continued with the imposition ofcriminal sanctions and vocational training as well as basic consideration of thejudge in the verdict against the defendant. The method used is the normative legal research. Source material used lawis the primary legal materials and secondary law, in this research, it has been known that the judicial inspection process inaccordance with the provisions of LawArticle 82 of RI Law. 23 Year 2002 About Child Protection Jo. RI Law No.35 of 2014 on Amendment to Law No. RI. 23 Year 2002 on Child Protection Jo. Article 64 paragraph (1) of the Criminal Code and basic legalconsideration by the judge in imposing punishment to the accused children weredivided into the basis for judicial and non-judicial basis.Keywords : Process of Juvenile Justice, Crime molestation